Accelerating Adaptation of Forest Trees to Climate Change Using Individual Tree Response Functions - Poupon, Valérie; Chakraborty, Debojyoti; Stejskal, Jan; Konrad, Heino; Schueler, Silvio; Lstibůrek, Milan (Frontiers in Plant Science, 2021)
In forest tree breeding, assisted migration has been proposed to accelerate the adaptive response to climate change. Response functions are currently fitted across multiple populations and environments, enabling selections of the most appropriate seed sources for a specific reforestation site. So far, the approach has been limited to capturing adaptive variation among populations, neglecting tree-to-tree variation residing within a population. Here, we combined the response function methodology with the in-situ breeding approach, utilizing progeny trials of European larch (Larix decidua) across 21 test sites in Austria ranging from Alpine to lowland regions. We quantified intra-population genetic variance and predicted individual genetic performance along a climatic gradient. This approach can be adopted in most breeding and conservation programs, boosting the speed of adaptation under climate change.